The origin of the Samaritans - Kartveit, Magnar, 1946- (Leiden ; Boston : Brill, 2009)
This book evaluates the methods often used for finding the origin of the Samaritans, assesses well known and new material, and suggests that the decisive event was the construction of the temple on Mount Gerizim in the first part of the fourth century b.c.e.
The legacy from Josephus -- State of the question -- Josephus and the origin of the Samaritans -- Josephus' predecessors -- Samaritan inscriptions and related texts -- The Pentateuch that the Samaritans chose -- The Samaritan attitude to the Prophets -- The origin of the Samaritans.
Includes bibliographical references (pages 371-392) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Josephus, Flavius -- Knowledge -- Samaritans; Josephus, Flavius; Bibel; Bibel; Qumrantexte; Josephus Flavius; Ioudaikē archaiologia; Altes Testament; Qumrantexte; Josephus, Flavius; Könige <Buch, II.> 17.; Antiquitates Judaicae; Samaritans -- Origin; Samaritain (peuple) -- Flavius Josèphe. "Antiquités judaïques."; samaritain (peuple) -- origines -- 7e s -- document; Samaritains -- Origines; RELIGION -- Judaism -- General; Samaritans; Entstehung; Jüdische Literatur; Samaritaner; Samaritaner